2020
DOI: 10.3390/cancers12071740
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Level of Circular RNA hsa_circ_0000190 Correlates with Tumor Progression and Poor Treatment Response in Advanced Lung Cancers

Abstract: Lung cancer (LC) causes the majority of cancer-related deaths. Circular RNAs (circRNAs) were reported to play roles in cancers by targeting pro- and anti-oncogenic miRNAs. However, the mechanisms of circRNAs in LC progression and their prognostic value of treatment response remain unclear. By using next generation sequencing (NGS) of LC cell lines’ transcriptomes, we identified highly overexpressed hsa_circ_0000190 and hsa_circ_000164 as potential biomarkers. By using the highly sensitive RT-ddPCR meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 53 publications
1
62
0
Order By: Relevance
“…DdPCR can overcome this shortcoming and be used instead of qPCR for the quantification of circRNA [207] . In addition, it has been shown that plasma levels of secretory circRNAs are detectable by RT-ddPCR in advanced lung cancers [208] .…”
Section: Available Strategies In Circrna Researchmentioning
confidence: 99%
“…DdPCR can overcome this shortcoming and be used instead of qPCR for the quantification of circRNA [207] . In addition, it has been shown that plasma levels of secretory circRNAs are detectable by RT-ddPCR in advanced lung cancers [208] .…”
Section: Available Strategies In Circrna Researchmentioning
confidence: 99%
“…Knockdown of circ_0061140 suppressed proliferation and migration in GC cells (Chen Q. et al, 2018). CDR1as expression is upregulated in OC tissues and it correlated with poor prognosis for TNM stages, lymph node metastasis, and reduced OS (Luo Y. H. et al, 2020). CDR1as sponges miR-641 causing up-regulation of ZEB1 and MDM2 expression to promote OC (Luo Y. H. et al, 2020).…”
Section: Ovarian Cancermentioning
confidence: 99%
“…CircRNA_0056616 was upregulated in tissues and plasma of LUAD patients and it was correlated with TNM stage and lymph node metastasis (He F. et al, 2020). Circ_0000190 and circ_000164 were overexpressed in plasma and tissues from LC patients and expression of circ_0000190 was associated with latestage, extra-thoracic metastasis, poor survival, and prognosis (Luo Y. H. et al, 2020). These exosomal circRNAs are easily detectable in liquid biopsy and may serve as potential biomarkers for LC (Luo Y. H. et al, 2020).…”
Section: Lung Cancer (Lc)mentioning
confidence: 99%
See 1 more Smart Citation
“…NEAT1 is also upregulated in MM, lung cancer and HCC, but is downregulated in acute promyelocytic leukemia [ 105 ]. Finally, Circ_0000190 is downregulated in MM and gastric cancer, whereas it displays overexpression in lung cancer [ 36 , 37 , 38 ]. These results highlight the cell- and tissue- specificity of lncRNAs, showing that their deregulation—and thus, their potential function—needs to be addressed in each tumor.…”
Section: Role Of Lncrnas In the Pathobiology Of MMmentioning
confidence: 99%